A randomized, open‐label, two‐period crossover bridging study on fuzuloparib capsules of different specifications in healthy Chinese volunteers. Issue 3 (26th August 2021) - Jiang, Xin; Tao, Ye; Liu, Yanping; Shi, Ping; Li, Ting; Sun, Feifei; Cao, Yu; Wang, Chenjing
Abstract : Aims: Fuzuloparib, also known as fluzoparib or SHR3162, is a poly ADP‐ribose polymerase (PARP) inhibitor developed for the treatment of malignant tumours. Three specifications of fuzuloparib capsules (10 mg, 40 mg and 100 mg) were originally developed for clinical trials. After the recommended dose was determined, a new specification of fuzuloparib capsule (50 mg) was produced for clinical use. This bridging study was conducted to determine the bioequivalence of the new specification to the three other specifications at the recommended dose. Methods: A single‐centre, randomized, open‐label, two‐period, crossover bridging study was conducted in 40 healthy Chinese subjects under fed conditions. Enrolled subjects received a single oral dose of test or reference preparations according to a randomization list in the first period and crossed over to receive the other preparations in the second period after a 6‐day washout interval. Blood samples were collected pre‐dose and post‐dose at specified time intervals. Plasma fuzuloparib concentrations were analysed by liquid chromatography‐mass spectroscopy (LC‐MS). A non‐compartment model was adopted to calculate pharmacokinetic parameters of investigational preparations. Primary PK parameters including area under the concentration–time curve (AUC) from administration to the last sampling time (AUC0‐ t ), AUC extrapolated to infinity (AUC0‐∞ ) and C max of test and reference preparations were compared to evaluate their bioequivalence. Results: The 90% confidence intervals (CIs) of geometric mean ratios of AUC0‐ t, AUC0‐∞ and C max were 96.99–104.95%, 97.03–104.93% and 96.53–108.98%, respectively, all of which were within the bioequivalence range of 80–125%. No serious adverse events were observed in this study and no subjects withdrew from the study due to adverse events. Conclusions: The test preparations were bioequivalent to the reference preparations. All investigational products were well tolerated.